Investigation of mec A and (tst-1) Genes Among Staphylococcus aureus Isolated from Skin Infection in Al- Diwaniyah Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study one handered and five samples were collected from skin infection in hospital DiwaniyahDermatology Consultancy in Al-Diwaniyah governorate. from December 2018 to April 2019. All sampleswere cultured and Identified by using phenotyping tests. The results revealed that 41 isolates were Staph. spp. and 30 Isolates out of them Diagnosed Staphylococcus aureus by using (API staph). Virulence factorswere explicated by using polymerase chain reaction (PCR) methicillin-resistant staphylococcus aureus ( MRSA ), were identified by detecting (mecA gene), which revealed that all skin infections were MRSA( 100 % ). Also, toxic shock syndrome toxin ( TSST ) were identified by using PCR to detect ( tst-1 gene 326bp.), which revealed that 23 isolate were positive out of 30 isolate ( 76.33 % ).